Semiconductor Solid‐Solution Nanostructures: Synthesis, Property Tailoring, and Applications - Liu, Baodan; Li, Jing; Yang, Wenjin; Zhang, Xinglai; Jiang, Xin; Bando, Yoshio (Small (Weinheim an der Bergstrasse, Germany), 2017)
The innovation of band‐gap engineering in advanced materials caused by the alloying of different semiconductors into solid‐solution nanostructures provides numerous opportunities and advantages in optoelectronic property tailoring. The semiconductor solid‐solution nanostructures have multifarious emission wavelength, adjustability of absorption edge, tunable electrical resistivity, and cutting‐edge photoredox capability, and these advantages can be rationalized by the assorted synthesis strategies such as, binary, ternary, and quaternary solid‐solutions. In addition, the abundance of elements in groups IIB, IIIA, VA, VIA, and VIIA provides sufficient room to tailor‐make the semiconductor solid‐solution nanostructures with the desired properties. Recent progress of semiconductor solid‐solution nanostructures including synthesis strategies, structure and composition design, band‐gap engineering related to the optical and electrical properties, and their applications in different fields is comprehensively reviewed. The classification, formation principle, synthesis routes, and the advantage of semiconductor solid‐solution nanostructures are systematically reviewed. Moreover, the challenges faced in this area and the future prospects are discussed. By combining the information together, it is strongly anticipated that this Review may shed new light on understanding semiconductor solid‐solution nanostructures while expected to have continuous breakthroughs in band‐gap engineering and advanced optoelectronic nanodevices. Semiconductor solid solution nanostructures are promising candidates for advanced optoelectronic nanodevices and clean energy harvesting. Recent progress in synthesis, fundamental properties and potential applications of semiconductor solid solution nanostructures is reviewed, and an overview of challenges and future perspectives is provided.